(untitled) (Euro-Latin American Journal of Administrative Law, 2014)
The quality of public services and public administrations and its evaluation have now moved to the foreground and play an important role in the framework of constant change these organizations are subject to in order to adapt to constant social, economic and technical changes, while at the same time operating under the principles of transparency, efficacy and responsibility. Undoubtedly, these auditing and evaluation techniques and values comprise a fundamental tool that will accompany the public administrations in their permanent updating and will contribute to offering better services to citizens. In short, we can affirm that quality evaluation is an essential tool for gaining knowledge of the performance and the effects of the service they offer and of their public interventions.